Implementation of Patient Mortality Reporting System at Ngudi Waluyo Wlingi Regional General Hospital with Interactive Dashboard Using Looker Studio - Rusdi, Achmad Jaelani; Suhariyono, Untung Slamet; Ma'roef, Moch. Noer Hoedan; Putri, Alya Nurryta (PROMOTOR, 2025)
Patient mortality reporting is an important component of hospital management because it reflects the quality of services and is the basis for evaluating health policies. Ngudi Waluyo Wlingi Regional General Hospital faces challenges in presenting mortality reports in an informative, fast, and accurate manner. This study aims to design and implement an interactive dashboard-based mortality reporting system using Looker Studio. Mortality data is collected through the Hospital Management Information System (SIMRS), exported to Google Sheets and then visualized in the Looker Studio dashboard. The main stages include data collection and pre-processing, simple system design (use cases and activity diagrams), and visualization creation. The result is an interactive dashboard display that presents mortality information in real-time, accurate, and easy-to-understand manners. This system is expected to improve the efficiency of monitoring, decision-making, and the quality of hospital services.